A new pebble game that characterizes parallel complexity classes - Venkateswaran, H.; Tompa, Martin (27th Annual Symposium on Foundations of Computer Science (sfcs 1986), 1986)
A new two-person pebble game that models parallel computations is defined. This game extends the two-person pebble game defined in [DT85] and is used to characterize two natural parallel complexity classes, namely LOGCFL and AG1. The characterizations show a fundamental way in which the computations in these two classes differ. This game model also unifies the proofs of some well known results of complexity theory.